2011
DOI: 10.1111/j.1468-3083.2011.04181.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic reports from 270 patients with multiple primary melanomas: a 34‐year single‐institution study

Abstract: Skin examination and long-term follow-up are mandatory for patients affected by melanoma, with the intent to promptly diagnose not only a disease progression but also possible new primary melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 23 publications
8
60
4
2
Order By: Relevance
“…In this study, we examined the relationship between MPM and SPC. The incidence of MPM in our population was 4%, which is consistent with the literature 3–5 . We found a female preponderance among patients with MPM, but a male preponderance among patients with MPM plus SPC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we examined the relationship between MPM and SPC. The incidence of MPM in our population was 4%, which is consistent with the literature 3–5 . We found a female preponderance among patients with MPM, but a male preponderance among patients with MPM plus SPC.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the risk of subsequent cancer is an important issue for patients with melanoma. In particular, there is a high risk of second primary melanoma, with an incidence of 1–8% 3–5 . Development of a second primary cancer (SPC) after a single primary melanoma (SPM) has been discussed in several studies, with a reported incidence of 1.5–20%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple primary melanomas (MPM) are diagnosed in 1.2% to 8.2% of patients with sporadic melanoma . Patients with melanoma are at approximately nine‐fold increased risk of developing an additional primary melanoma compared to the general population . The risk is higher within the first year but remains elevated for more than 20 years after first diagnosis supporting a continued long‐term surveillance in melanoma patients …”
Section: Introductionmentioning
confidence: 99%
“…Sunburn and intermittent sun exposure are the dominant environmental determinants of CMM risk, instead of large cumulative exposures of temperate climes (6,7). In addition to its increasing occurrence (3,(8)(9)(10) CMM patients seems to be at a greater risk of developing a second primary melanoma, non-melanoma skin cancers (NMSC), and primary noncutaneous malignancies compared with the general population (11)(12)(13)(14)(15)(16)(17)(18)(19). The aim of this study was to analyze the clinical features of patients with CMM in our area, characterized by a high proportion of European immigrant descendants.…”
Section: Introductionmentioning
confidence: 99%